Kecerdasan Emosional, Stres Akademik, dan Kesejahteraan Subjektif pada Mahasiswa - Sari Julika; Diana Setiyawati (Faculty of Psychology, Universitas Gadjah Mada, 2019)
The objective of this study was to understand the relationship between academic stress, emotional intelligence, and subjective well-being in college student. Hypothesis of the study was academic stress and emotional intelligence can predict someone’s subjective well-being. This study utilized a quantitative survey method. Participants of this study were 132 college students from different majors who lived in Yogyakarta, men and women, with ages varied from 18 to until the 30s. Measurement tools that utilized in the study were academic stress, emotional intelligence and student subjective well-being scales. Data were analyzed using regression analysis. Academic stress and emotional intelligence were found to predict someone’s subjective well being (F=9.862; p<0.001). Findings provide support that academic stress and emotional intelligence predict subjective well being.